Post-Pandemic Media Engagement: Understanding Student Communication Practices in a Transformed Educational Landscape - Yudha, Reza Praditya; Chaphichith, Xayapheth; Hakim, A. Rahman (Jurnal Komunikasi Pendidikan, 2025)
The pandemic has globally become a turning point for social change. Including, the learning process and communication practices becoming more integrated with digital media. This study aims to understand undergraduate students' engagement with media in the post-pandemic era in Indonesia. Drawing on mediatization, this study uses surveys, interviews, and students’ daily notes to collect data. The researcher then visualizes data using Nvivo. Informants are 92 undergraduate students who wrote a daily note from 16th March to June 6th, 2024. The findings show an interrelation between undergraduate students' social dynamics, communication practice, and media engagement. This study reveals distinct patterns in media engagement among Indonesian students that were not previously documented, particularly regarding their adaptation to hybrid learning environments. Government regulations regarding social restrictions do not limit students’ social interaction and learning process. Students’ social interaction and communication practice become more embedded into media usage. The communication practices that are increasingly engaging with media keep continuing even after the pandemic is over. Media are converged so that students do not adopt or are dominated by one type of media. Likewise, students can get information from different types of media.